Mapping Corruption Related Themes In Malaysia’s Local Government Audit Reports 2021 - 2024 - Adnan, Normala Mohd; Yusof, Hairuzzaki Mohd; Aminudin, Rabi’ah; Jamaiudin, Norhaslinda; Kaisi, Sherrif (Mauriduna : Journal of Islamic Studies, 2026)
Local governments are critical to effective public service delivery and democratic accountability, yet they frequently face governance challenges. This study systematically investigates thematic trends in corruption-related audit findings within Malaysian local councils, leveraging a qualitative thematic code co-occurrence mapping in ATLAS.ti 24. Drawing on Auditor General (AG) reports from 2021 to 2024, the analysis assesses audit findings across four geographically diverse Malaysian states, which constitute Selangor, Sabah, Johor and Kelantan. The findings reveal persistent structural weaknesses, mainly in procurement, planning and enforcement systems. The co-occurrence mapping indicates that Sabah and Selangor exhibit more pronounced high-risk zones, characterized by a complex interplay of systemic deficiency issues, while Johor and Kelantan expose distinct challenges related to oversight mechanisms and accountability frameworks. This research provides a data-driven understanding of prevalent governance gaps at the local level and highlights various administrative realities across states. The study suggests targeted and contextually adapted governance reforms that emphasize the necessity of strengthening internal controls and oversight capacities to foster greater integrity in Malaysian local government.